النمذجة التخالفية لنظام الفرملة (ABS) باستخدام سلاسل ماركوف - المحايري محمد; البستاني حسن; ملحم محمد (Latakia University Journal -Engineering Sciences Series, 2016)
تعد النظم المضمنة المقادة بالحدث (event driven embedded systems) أحد المكونات الأساسية للنظم المضمنة التخالفية (Heterogeneous Embedded Systems) ولتصميم هذه النظم نحن بحاجة إلى توصيفها على مستوى النظام (System level) عن طريق وضع نموذج تصميم عتادي برمجي مشترك قادر على استيعاب السلوك المختلف لكل من (HW, SW). هدف هذا البحث هو بناء نموذج تصميم مشترك (Discrete Event Co-design Model) على أساس سلاسل ماركوف (Markov chains) قادر على توصيف النظم المقادة بالحدث، ومن ثم استخدام النمذجة التخالفية عن طريق تضمين النمذجة المقطعة زمنياً (Discrete time modeling ) ضمن النموذج (Discrete Event Model) بغرض تطبيقه على نظام الفرملة (ABS)Anti-lock Braking System . ولتحقيق هذا النموذج نستخدم (PtolemyII) و هو إطار برمجي مبني على أساس لغة Java، من إنتاج (University of California, Berkeley) كجزء من مشروع Ptolemy. وتأتي أهمية هذا البحث ليكون كنواة للحصول على نموذج تصميم مشترك للنظم المضمنة التخالفية في الأعمال المستقبلية. Event driven embedded systems are one of the essential structures of heterogeneous embedded systems. The difference behavior of hardware and software motivates the usage of high-level system design approaches such as Hardware Software co-design Model. The objective of this paper is to obtain a new Co-design model for discrete-events embedded systems based on Markov chains, and then using the heterogeneous modeling by composing the discrete-times model within discrete-events model to apply it on anti‐lock braking system (ABS). To achieve the model, we use Ptolemy II which is a Java-based software framework developed as part of the Ptolemy Project by University of California, Berkeley. The importance of this paper is to be the kernel for heterogeneous co-design modeling for heterogeneous embedded systems in future works.